Relationship between the electron-transfer coefficients of the oxygen reduction reaction estimated from the Gibbs free energy of activation and the Butler–Volmer equation - Maurya, Rajan; Das, Rubul; Tripathi, Anand Kumar; Neergat, Manoj (Physical chemistry chemical physics : PCCP, 2022)
The rate of electron-transfer reactions, irrespective of whether electrochemical or electrocatalytic, is universally explained on the basis of Butler–Volmer (B–V) theory. The charge-transfer coefficient ( α ) obtained is typically in the range of 0.0–1.0, and is 0.6 ± 0.1 for the oxygen reduction reaction (ORR) on Pt, which is the subject of the present investigation. Alternatively, α can be estimated from the derivative of the change in Gibbs free energy of activation (Δ G # ) with respect to the overpotential ( η ) and has the unreasonably high value of 1.1 ± 0.2. The origin of the difference in the α values obtained from these two methods is investigated. The value of α greater than 1.0 stems from the alternative potential-dependent lower energy barrier path for the formation of the activated complex, offered by the electrified catalyst surface. For the electrocatalytic reaction, the α value derived from the Δ G # is the true kinetic parameter. The theoretical background of such processes is presented to justify our claims.